Folding and inversion tectonics in the Anti-Atlas of Morocco - Helg, Urs; Burkhard, Martin; Caritg, Séverine; Robert-Charrue, Charles (My University, 2004)
The late Variscan Anti-Atlas of Morocco shows some conspicuous deviations from the standard anatomy of foreland fold-and-thrust belts. Large basement inliers crop out at a very short distance of less than 50 km behind the southeastern front of the fold belt, reminiscent of Windriver-style basement uplifts. In contrast to the Rocky Mountain foreland, however, the Anti-Atlas basement uplifts punctuate tightly folded Paleozoic cover series similar in tectonic style to the Appalachian Valley and Ridge province. Cover shortening is exclusively accommodated by buckle folding, and the Anti-Atlas fold belt lacks any evidence for duplexing or thrust faults other than the occasional steep reverse fault found near basement inliers. Basement domes have classically been considered as the result of vertical tectonics in a horst and graben fashion, or, alternatively, as large “plis de fond” [ Argand, 1924 ], basement folds. Unfolding of a large portion of an Ordovician quartzite marker bed reveals a minimum shortening of 17% (30 km). Balancing this section at the crustal scale indicates a lower crustal detachment level at 18 to 25 km depth. Basement shortening is inferred to be accommodated through massive inversion of former extensional faults, inherited from a Late Proterozoic-Lower Cambrian rifting phase.
Keywords: Anti-Atlas; tectonics; balanced cross section; folding; foreland fold and thrust belt